Prevalence and influencing factors of chronic diseases and chronic multimorbidity among Uygur rural adults: a cross-sectional survey in Xinjiang Production and Construction Corps - Yaoyao CHEN; Rulin MA; Heng GUO; Xianghui ZHANG; Xinping WANG; Jia HE; Yu LI; Shuxia GUO (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the prevalence and influencing factors of chronic diseases and chronic multimorbidity among Uygur rural adult residents in Xinjiang Production and Construction Corps (Xinjiang). MethodsUsing typical sampling, we recruited 14 851 Uygur rural residents aged ≥ 18 years in Xinjiang and conducted face-to-face interview with a self-designed questionnaire, physical examination, and laboratory tests among the residents during August - September 2016. Multivariate logistic regression model was used to analyze influencing factors of chronic diseases and chronic multimorbidity among the residents. ResultsOf the 12 792 eligible participants, 8 937 (69.9%) were identified as having chronic diseases and 5 770 (45.1%) having chronic multimorbidity. The three diseases most frequently identified among the participants were metabolic syndrome (identified in 33.1% of the participants), dyslipidemia (30.8%), and hypertension (29.9%); the observed top three multimorbidities of two chronic conditions were dyslipidemia and hypertension (observed in 12.2% of the participants), metabolic syndrome and fatty liver (9.7%), and dyslipidemia and fatty liver (8.8%); and the observed top three multimorbidities of three chronic conditions were metabolic syndrome, dyslipidemia and fatty liver (6.8%), metabolic syndrome, hypertension and fatty liver (6.0%), and metabolic syndrome, hypertension and musculoskeletal disorder (4.4%). The results of multivariate logistic regression analysis revealed following risk factors for chronic diseases and chronic multimorbidity: aged 40 years or older, being married or divorced or widowed, with family history of chronic diseases, being obesity or overweight, and having central obesity; while, having the education of primary school and above was a protective factor against chronic diseases and chronic multimorbidity. ConclusionThe prevalence of chronic diseases and chronic multimorbidity were high and mainly influenced by age, education, marital status, family history of chronic disease, obesity or overweight, and central obesity among Uygur rural adults in Xinjiang.